Mechanical Properties of High-Performance Lightweight Aggregate Concrete with Inorganic Polymers Cement Based on Multiple Minerals under Uniaxial Loading - Xiao Ma; Qiuhua Rao (Advances in Materials Science and Engineering)
High-performance lightweight aggregate concrete with inorganic polymers cement based on multiple minerals is a very promising new material. The research of mechanical properties of the new material is of great theoretical and practical significance. In this research, the failure behavior, cubic and prism compressive strength, elastic modulus, peak strain of the new material, and the nature of the stress-strain curve are studied. An analytical model is quoted to represent the ascending and descending parts of the stress-strain curve.